Epidermophyton floccosum as apossible aethiological agent of tinea capitis: a case report - Rudi Chandra; Nova Z Lubis (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Tinea capitis is a superficial fungal infection of scalp that affects particularly school-aged children. It is usually caused by dermatophytes, although Epidermophyton floccosum can cause the tinea capitis. Tinea capitis caused by the E. floccosum is quite interesting because it can confirm the sporadic occurrence of hair parasitism by this dermatophyte. In this article, it was reported tinea capitis caused by E. floccosum. A 15-year-old girl, presented with itchy scaly alopecia on scalp since 1 week ago. The patient denied any contact with cat or dog, and there was not any family history. On physical examinations, lymphadenopathies were found at both lateral neck and alopecia with scales and crusts, lenticular to nummular sizes, at scalp. Hair-pull test was positive. The trichoscopy examination found comma hairs, broken hairs, and black dots. The fungal culture examination discovered the growth of E. floccosum. The patient was diagnosed with tinea capitis and treated with 500 mg of griseofulvin orally, 10 mg of cetirizine orally, and 2% of ketoconazole shampoo. Epidermophyton floccosum is an anthropophilic dermatophyte that frequently causes tinea cruris, tinea pedis, tinea corporis and onychomycosis, but not tinea capitis. Several reports have showed the capability of E. floccosum in perforating hairs and causing tinea capitis. In conclusion, E. floccosum is a possible aethiological agent of tinea capitis through its ability to perforate hairs.